Glucose-6-phosphate dehydrogenase activity, structure, molecular characteristics and role in neonatal hyperbilirubinemia in cord blood in Cukurova region - Ozlü, Ferda; Satar, Mehmet; Menziletoğlu-Ylldlz, Sule; Unlükurt, Isa; Aksoy, Kiymet (The Turkish Journal of Pediatrics, 2011)
The most common causes of neonatal indirect hyperbilirubinemia are blood incompatibility and erythrocyte enzyme defects. Glucose-6-phosphate dehydrogenase (G6PD) is a guarantee of erythrocyte stability and capability of existence of red cells. We present here the results of a study on the effect of enzyme kinetics and different mutations on neonatal hyperbilirubinemia in the Cukurova region. Two hundred healthy term male neonates born in Cukurova University Balcall Hospital, Adana Maternity Hospital and Cukurova Maternal and Children’s Hospital between 1 November 2004 and 30 November 2007 were consecutively studied. Nanogen DNA microarray was used to determine Gd Union, Gd San, Gd Mediterranean, and Gd San Antonio mutations. Quantitative G6PD enzyme assays were performed. Glucose-6-phosphate dehydrogenase deficiency was detected in six out of 200 male neonates (3%). The other 194 neonates had normal G6PD activity, with a mean of 8.3 +/- 2.1 IU/g hemoglobin (Hb) (5.2-12.7 IU/g Hb). Clinical follow-up, enzyme kinetics and genetic studies were performed in the G6PD-deficient neonates. Differences were observed in clinical outcomes, rates of bilirubin decline and maximum total bilirubin levels in the neonates having the same mutation. These differences might be caused by the effects of kinetic variant on the hyperbilirubinemia without the direct effect of the mutation. In future studies, mutation analyses of further G6PD-deficient cases may address the genotype differences and their clinical effects in G6PD-deficient patients.